IS A RED CARD FOR LEARNERS’ USE OF THEIR L1 IN L2 LESSONS FAIR? A SOCIOCULTURAL ACCOUNT - Canh, Le Van; Hang, Pham Thi (VNU Journal of Foreign Studies, 2019)
One of the controversial issues in second language acquisition research is the role of learners’ first language in their second language learning. Traditionally, first language was assumed to get in the way or interfere with the learning of the L2, and therefore, the first language must be banned in the foreign language classroom. However, this view has recently been reexamined and questioned by empirical studies conducted within the sociocultural perspectives. The goal of this paper is to provide new insights into the mediating role of the first language by reviewing those studies. The paper suggests that L1, when appropriately and systematically used, can be an enabling tool that scaffolds learners in completing cognitively complex and demanding L2 learning tasks. Towards this goal, research directions are also suggested. However, it is important to note that this paper is not intended to encourage teachers and learners to use the L1 in the L2 classroom unsystematically and inappropriately; rather its goal is to encourage teachers to research their classroom in order to find optimal and effective use of L1 for mediating the success of L2 learning.